Microcystin-LR Induced Apoptosis in Rat Sertoli Cells via the Mitochondrial Caspase-Dependent Pathway: Role of Reactive Oxygen Species - Huang, Hui; Liu, Chuanrui; Fu, Xiaoli; Zhang, Shenshen; Xin, Yongjuan; Li, Yang; Xue, Lijian; Cheng, Xuemin; Zhang, Huizhen (Frontiers in Physiology, 2016)
Microcystins (MCs), the secondary metabolites of blue-green algae, are a ubiquitous and major cyanotoxin contaminant. Besides the hepatopancreas/liver, the reproductive system is regarded as the most important target organ for MCs. Although reactive oxygen species (ROS) have been implicated in MCs-induced reproductive toxicity, the role of MCs in this pathway remains unclear. In the present study, Sertoli cells were employed to investigate apoptotic death involved in male reproductive toxicity of microcystin-LR (MC-LR). After exposure to various concentrations of MC-LR for 24 h, the growth of Sertoli cells was concentration-dependently decreased with an IC50 of approximately 32 μg/mL. Mitochondria-mediated apoptotic changes were observed in Sertoli cells exposed to 8, 16 and 32 μg/mL MC-LR including the increased expression of caspase pathway proteins, collapse of mitochondrial membrane potential (MMP) and generation of ROS. Pretreatment with a global caspase inhibitor was found to depress the activation of caspases, and eventually increased the survival rate of Sertoli cells, implying that the mitochondrial caspases pathway is involved in MC-LR-induced apoptosis. Furthermore, N-acetyl-l-cysteine (NAC) attenuated the MC-LR-induced intracellular ROS generation, MMP collapse and cytochrome c release, resulting in the inhibition of apoptosis. Taken together, the observed results suggested that MC-LR induced apoptotic death of Sertoli cells by the activation of mitochondrial caspases cascade, while its effects on the ROS-mediated signaling pathway may contribute towards the initiation of mitochondrial dysfunction.